Ethics and Welfare in invertebrates: a stepping-stone to research and animal production - Crespi-Abril, Augusto C.; Rubilar, Tamara (Revista de Biología Tropical, 2023)
Introduction: Even though only a few species are considered to be dangerous, pests or vectors, the majority of invertebrates produce a feeling of aversion in humans. This has contributed to the delay in the development of ethical considerations as regards this group in contrast with vertebrates, with the exception of cephalopods. Objective: In the present study, we provide an overview of the current situation on animal ethics and welfare in order to contribute to the development of a framework for ensuring invertebrate welfare. Methods: Today, animal welfare is multidisciplinary in nature to a very high degree as it includes ethology, physiology, pathology, biochemistry, genetics, immunology, nutrition, cognitive-neural, veterinary medicine, and ethics. Animal welfare is a complex concept, difficult to achieve successfully from one perspective. Results: As a consequence, we propose to include the five domains (nutrition, environment, health, behaviour and mental state) along with the three conceptions (basic health and functioning, affective state and natural living), as well as the 5R Principle (Replace, Reduction, Refinement, Respect and Responsibility) in seeking to achieve a comprehensive welfare state. Conclusions: We consider that in both research and animal production, the individual and collective ethical concerns coexist and, in fact, the main moral concern to account for is the collective one and that, within that collective view, the individual moral concern should be applied with responsibility and respect for the individual. Finally, we propose a practical example of invertebrate welfare production in sea urchin aquaculture with the aim of including animal production of invertebrates in this important discussion.